Cellular requirements for iron–sulfur cluster insertion into the antiviral radical SAM protein viperin - Upadhyay, Arunkumar S. (J Biol Chem, 2017)
Viperin (RSAD2) is an interferon-stimulated antiviral protein that belongs to the radical S-adenosylmethionine (SAM) enzyme family. Viperin's iron–sulfur (Fe/S) cluster is critical for its antiviral activity against many different viruses. CIA1 (CIAO1), an essential component of the cytosolic iron–sulfur protein assembly (CIA) machinery, is crucial for Fe/S cluster insertion into viperin and hence for viperin's antiviral activity. In the CIA pathway, CIA1 cooperates with CIA2A, CIA2B, and MMS19 targeting factors to form various complexes that mediate the dedicated maturation of specific Fe/S recipient proteins. To date, however, the mechanisms of how viperin acquires its radical SAM Fe/S cluster to gain antiviral activity are poorly understood. Using co-immunoprecipitation and (55)Fe-radiolabeling experiments, we therefore studied the roles of CIA2A, CIA2B, and MMS19 for Fe/S cluster insertion. CIA2B and MMS19 physically interacted with the C terminus of viperin and used CIA1 as the primary viperin-interacting protein. In contrast, CIA2A bound to viperin's N terminus in a CIA1-, CIA2B-, and MMS19-independent fashion. Of note, the observed interaction of both CIA2 isoforms with a single Fe/S target protein is unprecedented in the CIA pathway. (55)Fe-radiolabeling experiments with human cells depleted of CIA1, CIA2A, CIA2B, or MMS19 revealed that CIA1, but none of the other CIA factors, is predominantly required for (55)Fe/S cluster incorporation into viperin. Collectively, viperin maturation represents a novel CIA pathway with a minimal requirement of the CIA-targeting factors and represents a new paradigm for the insertion of the Fe/S cofactor into a radical SAM protein.